The Quest of Identity of Kafka Tamura in Haruki Murakami’s Kafka on The Shoreflood in The Indonesian Online Newspapers: A Multimodal Critical Discourse Analysis of The Representation of Flood - Luciyana Dwiningrum (Universitas Pendidikan Indonesia (UPI), 2014)
This present study examines the representation of flood in Indonesian online newspapers verbally and visually by using Kress and van Leeuwen’s framework (2006) and Systemic Functional Linguistics as proposed by Halliday (1994). This study employed a qualitative method to describe the representation and its signification. The collected data were analysed from kompas.com, republika.co.id, radarcirebon.com, and harianjogja.com online newspapers. The data were in the form of words, phrases, and sentences and pictures. This study, verbally, found that flood was represented as actor (14) or 60.9%, goal (5) or 21.7%, carrier (2) or 8.7%, and phenomenon (2) or 8.7%. The processes used are material (19) or 65.5%, flood as material process (3) or 10.3%, relational: attributive (3) or 10.3%, relational: identifying (1) or 3.4% mental: perceptive (1) or 3.4%, and mental: cognitive (2) or 6.9%. Furthermore, flood is also represented as circumstance of time (4) or 66.7%, circumstance of condition (1) or 16.7%, and circumstance of reason (1) or 16.7%. Visually, flood was represented as an actor which does a damaging action, a circumstance of time which was waited by several people to get new jobs such as ojek rider, and a goal which was considered to be a swimming pool and a new playground in Jakarta. Keywords: Representation, Multimodal Critical Discourse Analysis, Systemic Functional Linguistics, and Online NewspapersKeywords: Representation, Multimodal Critical Discourse Analysis, Systemic Functional Linguistics, and Online Newspapers